سدّ الذّرائع و تطبيقاته في المجال الاقتصادي حول أموال المساجد و حكم مطعم كافّي على انتشارها بشكل واسع - Gistav Rainhard; Erwandi Tarmizi (Economic Reviews Journal, 2026)
Islamic legal sources are divided into two categories: those unanimously accepted by scholars and those subject to scholarly disagreement. Among the latter is the principle of blocking the means (sadd al-dharā’i‘), which prohibits permissible acts that may lead to prohibited outcomes. This principle serves as a fundamental legal maxim in Islamic jurisprudence, facilitating the derivation of rulings for contemporary social and economic issues. This study aims to clarify the concept and legitimacy of the sadd al-dharā’i‘ principle and to analyze its application in economic contexts through two contemporary cases: depositing mosque donations in banks and the rise of café-style restaurants near mosques. The researcher employs a descriptive-analytical method based on classical and modern jurisprudential sources. The findings indicate that distributing surplus mosque funds to the needy is preferable to hoarding or depositing them without necessity, as preventing harm takes precedence over achieving benefit. Moreover, café-style restaurants associated with entertainment and gender mixing are deemed reprehensible due to their potential to promote social impropriety.